Magnetic properties of sintered CoFe2O4-BaTiO3 particulate magnetoelectric composites - Mohan, S.; Joy, P. A. (Ceramics International, 2019)
The magnetic properties of sintered particulate magnetoelectric CoFe2O4 - BaTiO3 composites have been studied. The particulate composites are sintered in the temperature range 1000-1300 degrees C, for a short duration of 10 min. The magnetic transition temperature (T-c) of CoFe2O4 is found to decrease with increasing the sintering temperature and sintering time, as well as on increasing the BaTiO3 content in the composites. Similarly, a reduced saturation magnetization at room temperature, compared to that expected for the CoFe2O4 content, is also observed. Powder X-ray diffraction studies showed the presence of the impurity phase related to the hexagonal ferrite BaFe12O19 in all the composites. Ba2Fe2Ti4O13 is observed as a second impurity phase in the BaTiO3 - rich composites. The present studies suggest that the composition of the piezomagnetic (CoFe2O4) phase in the CoFe2O4 - BaTiO3 magnetoelectric composite is affected during the sintering process.
Keywords: composites; magnetic properties; Sintering